2022
DOI: 10.1021/acs.cgd.2c00084
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Mechanistic Study of Crystal Nucleation Inhibition in a Supersaturated Drug Solution by Polyvinylpyrrolidone

Abstract: In this study, the molecular states of supersaturated drugs and crystallization inhibitors in aqueous solutions were characterized using NMR to elucidate the inhibition mechanism of drug crystal nucleation in drug-supersaturated solutions. Polyvinylpyrrolidone (PVP) K12, PVP K25, and 1-ethyl-2-pyrrolidone (NEP) were used as additives to evaluate their ability to inhibit chlorthalidone (CLT) crystal nucleation. Although an inhibitory effect of NEP on the crystal nucleation of CLT was not observed, PVP effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Based on these data, it was observed that the WSC solution could effectively hinder the crystal growth and reduce nucleation of AM; thus, elevated levels of supersaturation could be maintained for extended periods of time. Polymeric additives have been widely utilized in supersaturated formulations because of their ability to inhibit drug crystallization [ 10 ]. It has been reported that polymers stabilize drugs in supersaturated solutions by intermolecular interactions between drugs and polymers, thus inhibiting drug crystal nucleation in the long term [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these data, it was observed that the WSC solution could effectively hinder the crystal growth and reduce nucleation of AM; thus, elevated levels of supersaturation could be maintained for extended periods of time. Polymeric additives have been widely utilized in supersaturated formulations because of their ability to inhibit drug crystallization [ 10 ]. It has been reported that polymers stabilize drugs in supersaturated solutions by intermolecular interactions between drugs and polymers, thus inhibiting drug crystal nucleation in the long term [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, various strategies have been developed to improve solubility such as amorphous solid dispersions [ 4 , 5 ], cocrystals, and [ 6 , 7 ] co-amorphous systems [ 8 , 9 ]. These formulation techniques can create the drug in the supersaturation state [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, they selected polyvinylpyrrolidone (PVP) K12, PVP K25, and 1ethyl-2-pyrrolidone (NEP) as additives and investigated the reasons for their inhibition of chlorthalidone (CLT) crystallization nucleation by using NMR technology. 50 The results showed that PVP could inhibit the crystallization of CLT and keep its solution supersaturated. NMR results showed that the presence of PVP could keep CLT supersaturated for a long time, and the presence of PVP K25 significantly inhibited the molecular mobility of supersaturated CLT.…”
Section: Methodologies and Strategies For Crystallization Inhibitionmentioning
confidence: 98%
“…They found that hypromellose distributed in amorphous nanodroplets that were rich in ibuprofen molecules strongly inhibited the mobility of ibuprofen molecules. Later, they selected polyvinylpyrrolidone (PVP) K12, PVP K25, and 1-ethyl-2-pyrrolidone (NEP) as additives and investigated the reasons for their inhibition of chlorthalidone (CLT) crystallization nucleation by using NMR technology . The results showed that PVP could inhibit the crystallization of CLT and keep its solution supersaturated.…”
Section: Methodologies and Strategies For Crystallization Inhibitionmentioning
confidence: 99%